Seleção, comportamento fenotípico e genotípico e desenvolvimento de uma nova cultivar de manjericão (Ocimum basilicum L.) para Sergipe. - Souza, Evanildes Menezes de (2007)
Basil is a medicinal, aromatic and spicy species with high commercial value. Actually, the production is based on the cultivation of a mix of chemical types and that cause production of low quality essential oil. The study of genetic parameters, which influence essential oil production and chemical constituents, contribute for development of cultivars with high yield and quality. The aim of the work was the selection and evaluation of the phenotypic and genotypic behavior as well the developing of a basil cultivar (Ocimum basilicum L.) adapted in Brazilian northeast region with higher content and yields of essential oil, which presents a large amount of linalool. In the first step the accessions were evaluated and selection was realized based on individual plants at generations S0 (original population), S1 and S2, which were selfed. It has analyzed essential oil content and linalool content in the essential oil. For both variables it has observed significative increase of production with gains up to 234% for essential oil content and 71% of linalool content, which indicate efficiency of the selection process. Genetic variance and herdability estimatives associated to the high yield values indicate the possibility to develop a new basil cultivar adapted for the São Cristóvão-SE county. In the second step of this work we obtained some genetic parameters associated with the production behavior of six basil populations, cultivated in 2004/05 and 2005/06. The variables dry weight of leaves + inflorescences and essential oil yields presented higher variability because of strong influence of the studied years. This was not observed for linalool content, which maintained its values stable for the two years. All the characters presented high herdabilities by the combined analyses, indicating high genetic control and great possibilities to transmit them to the future generations. The combined analyses showed highest essential oil content and yield for the populations PI 197442-S3-bulk 3, PI 197442-S3-bulk 5 e PI 197442-S3-bulk 8. For the major chemical constituent of the essential oil, linalool, all the populations presented similar behavior. Only the minor chemical constituents were different. This work terminated with the development of the basil cultivar Maria Bonita .